Synthesis, Crystal Structure of Zinc Complex with 3-Hydroxy-1-adamantanecarboxylic Acid - Zhao, Guo-Liang; Wu, Xiao-Yong; Guan, Quan-Yin; Shen, Jin-Bei (Asian Journal of Chemistry, 2012)
A novel zinc(II) complex, [Zn(HOC10H14COO)2(1,10-phen)]·6H2O (1) was synthesized by hydrothermal method from zinc hydroxide, 1,10-phenanthroline and 3-hydroxy-1-adamantane acid (C10H14(HO)COOH). It was characterized by IR spectrum, elemental analysis and thermogravimetric analysis. Its crystal structure was determined by single crystal diffraction technique. The complex, C34H50N2O12Zn, crystallizes in the monoclinic system, space group P21/c with a = 1. 25822(6) nm, b = 0.72825(2) nm, c = 2.63620(6) nm, b = 106.067(1)°,V = 3.50999(19) nm3, Z = 4, Mr = 744.15, F(000) = 1576, Dc = 1.408 mg cm-3, μ(Mo Ka) = 0.765 mm-1. CCDC: 757154.